Towards Green and Low-Carbon Development in Chinese Cities. (November 2022) - Chen, Meian; Yang, Li; Hu, Min; Montero, Diego
This article presents an indicator system called Low-Carbon and Green Index for Cities (LOGIC) that evaluates the performance of Chinese cities in terms of low-carbon development and identifies areas for improvement. This system issues a score ranging from 0 to 100, with a higher score indicating a better performance in lower carbon growth within a specified time period. LOGIC was applied to a sample of 115 Chinese cities representing a diverse range of population sizes, income levels, geographies and stages of economic and urban growth between 2010 and 2015. The results of this study indicate that these cities have made progress in green and low-carbon development. In addition, more than 90 of the 115 sampled cities experienced GDP growth alongside LOGIC score growth over the selected period, showing that green and low-carbon goals are not antithetical to good economic performance. The average overall index score for all 115 Chinese cities in 2015 was 44.9 out of 100, reflecting China's heavy reliance on coal and its energy-intensive economy. Low-carbon pilot cities had an average overall index score of 47.0 in 2015 compared to an average of 42.9 for non-pilot cities. These LOGIC results suggest that transforming city economies away from energy-intensive towards high-tech and service industries could facilitate their low-carbon and green growth. This article uses the city of Wuhan as a case study to illustrate the application of LOGIC and its utility in assessing city-level low-carbon efforts.